2014
DOI: 10.1128/aem.01146-14
|View full text |Cite
|
Sign up to set email alerts
|

Benzoate Metabolism Intermediate Benzoyl Coenzyme A Affects Gentisate Pathway Regulation in Comamonas testosteroni

Abstract: A previous study showed that benzoate was catabolized via a coenzyme A (CoA)-dependent epoxide pathway in Azoarcus evansii (R. Niemetz, U. Altenschmidt, S. Brucker, and G. Fuchs, Eur. J. Biochem. 227:161-168, 1995), but gentisate 1,2-dioxygenase was induced. Similarly, we found that the Comamonas testosteroni strain CNB-1 degraded benzoate via a CoA-dependent epoxide pathway and that gentisate 1,2-dioxygenase (GenA) was also induced when benzoate or 3-hydroxybenzoate served as a carbon source for growth. Genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 53 publications
0
24
0
Order By: Relevance
“…Only the ben/cat pathway is active under the conditions used in this work, since the C. pinatubonensis ⌬benA mutant does not grow on Bz and accumulates Bz (24). This dismisses possibilities such as benzoyl-CoA-type intermediates (generated during Box pathway operation) repressing the expression of genes involved in the degradation of some of the other AC tested here, which has been demonstrated for Box intermediates controlling the degradation of gentisate in Comamonas testosteroni (51).…”
Section: Figmentioning
confidence: 91%
“…Only the ben/cat pathway is active under the conditions used in this work, since the C. pinatubonensis ⌬benA mutant does not grow on Bz and accumulates Bz (24). This dismisses possibilities such as benzoyl-CoA-type intermediates (generated during Box pathway operation) repressing the expression of genes involved in the degradation of some of the other AC tested here, which has been demonstrated for Box intermediates controlling the degradation of gentisate in Comamonas testosteroni (51).…”
Section: Figmentioning
confidence: 91%
“…To investigate if our system can be used to analyze chemotactic responses of indigenous microbial species in a non-invasive and label-free manner, non-labelled Comamonas testosteroni CNB-1 was selected and tested with 4-hydroxybenzoic acid ( p -HBA) as its chemo-attractant. CNB-1 was isolated from sewage sludge of a wastewater-treatment plant from a chemical factory producing chloronitrobenzene 36 . Previous studies using swarm plate assays showed that CNB-1 exhibited strong chemotactic responses toward various aromatic compounds, including p -HBA 37 .…”
Section: Resultsmentioning
confidence: 99%
“…E. coli strains were cultivated at 37 °C in Luria Bertani (LB) medium with 100 μg/mL ampicillin. CNB-1 was cultivated at 30 °C in mineral salt broth (MSB) as previously described 36 . All the cells in the seed culture were harvested at the exponential phase, centrifuged and suspended in 1 × PBS containing 0.1 mmol/L EDTA as the pre-sample.…”
Section: Methodsmentioning
confidence: 99%
“…There is an increasing number of regulators, i.e. PaaR ( 63 ) (TetR family), CouR, FerC, HcaR, FerR, and GenR (MarR family) ( 27 , 64 67 ), PaaX (GntR family) ( 38 ), and BzdR and BoxR(XRE family) ( 17 , 20 ), that control aromatic degradation pathways and recognize aromatic CoA thioesters as inducers. Thus, FerR/FerC recognize feruloyl-CoA; CouR/HcaR recognize p -coumaroyl-CoA; BzdR/BoxR/GenR recognize benzoyl-CoA; and PaaX/PaaR recognize phenylacetyl-CoA.…”
Section: Discussionmentioning
confidence: 99%